Unification Requirements of Electric Vehicle Charging Infrastructure - Khalil Salah; Nazri Kama (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
By increasing electric vehicles in numbers and getting the public attention, availability, safety and accessibility of its charging infrastructure are key factors to users’ satisfaction. Charging infrastructure in electric vehicle industry can have a role as an interface for exchanging information among other components as well. Currently, lack of universality in electric vehicle industry has caused an isolation in networks of electric vehicles. This isolation will cause difficulty in having an aggregated set of information about electric vehicles and their consumption pattern. The paper reviews current charging infrastructure and the possibility of providing universality based on candidate protocols and technologies.